Estrogenic post-menopausal anti-osteoporotic mechanism of Achyranthes aspera L.: Phytochemicals and network pharmacology approaches - Moyeenul Huq, A. K. M.; Stanslas, Johnson; Nizhum, Nisarat; Uddin, Md. Nazim; Maulidiani, Maulidiani; Roney, Miah; Faridah, Abas; Jamal, Jamia Azdina (Elsevier Ltd, 2024)
Hormone replacement therapy is used to treat postmenopausal syndrome caused by estrogen deficiency, but it has been linked to an increased risk of breast cancer. In India, Achyranthes aspera L. is traditionally used to treat menstrual problems; however, there is a lack of mechanistic evidence of its phytoestrogenicity. Therefore, this study investigated the estrogenic activity of A. aspera on estrogen-responsive MCF-7 breast cancer cells. In a cell proliferation assay, the MeOH fraction (100 μg/mL) exhibited the highest proliferation effect (PE) of 138 % (p < 0.001) and relative proliferation effect (RPE) of 96.5 %, compared to 17β-estradiol (0.01 μM: 143 % PE, p < 0.001; 100 % RPE). The MeOH fraction was shown to upregulate the oestrogen marker genes trefoil factor 1 and progesterone receptor by 20.14–23.94 folds and 10.83–14.83 folds, respectively. Twelve phenolics were identified by LC-MS/MS in the active MeOH fraction, i.e. quinic acid, kaempferol hexoside, kaempferol 3-O-(2″-O-galloyl)-glucoside)-β-D-glucoside, geniposide, 3-O-(6′-O-(9Z,12Z-octadecadienoyl)-β-D-glucopyranosyl)-stigmast-5,22E-dien-3β-ol, kaempferol-3-O-glucoside (astragalin), 3,30-di-O-methylellagic acid isomer, procyanidin, naringin, propapyriogenin A2, (3β,22E,24R)-23-methylergosta-5,7,22-trien-3-ol and 6-prenylapigenin. Through network pharmacology, the potential effects, and mechanisms of these compounds in osteoporosis were revealed. About 55 target genes were linked to osteoporosis. GO and KEGG enrichment suggest regulation of female reproductive hormone related signaling pathways, which are also associated with estrogen dependent osteoporosis. Molecular docking analysis of the compounds revealed potential interactions with hERα receptor for 3-O-(6′-O-(9Z,12Z-octadecadienoyl)-β-D-glucopyranosyl)-stigmast-5,22E-dien-3β-ol and kaempferol-3-O-glucoside (astragalin) (docking scores of −9.3 and −10.1 kcal/mol, respectively) as compared to 17β-estradiol (−9.3 kcal/mol). These results suggest the estrogenicity of A. aspera via an ERα-associated mechanism and support its traditional usage in the management of menopausal-related problems.